Calculating joint queue length distributions in product form queueing networks - Silva, Edmundo Albuquerque de Souza e (2017)
Submitted by Elaine Almeida (elaine.almeida@nce.ufrj.br) on 2017-03-17T12:27:49Z No. of bitstreams: 1 05_88_000040345.pdf: 1103587 bytes, checksum: 19c507754d59ea7c90ef44e609a8256d (MD5)